Occupational Accidents in Iran: Risk Factors and Long Term Trend (2007–2016) - Izadi, Nazanin (J Res Health Sci, 2019)
Background: Although much is known about the distribution of occupational accidents in the world, less is known about occupational injuries in developing countries. Therefore, the aim of this study was to investigate the trend of occupational accidents during 10 years (2007-2016) and to find factors affecting the accident outcome. Study design: A cross-sectional study. Methods: This study was done based on the data gathered by the Iranian Social Security Organization (ISSO), including demographic data (age, sex, marital status) and occupational accident characteristics (accident sector, cause, type, body part, location, time, month, and incident outcome). Result: A decreasing pattern of occupational accidents was found from 2.95 per 1000 workers in 2007 to 1.46 per 1000 workers in 2016. The mean age of injured workers was 32.97 years. The most common cause and type of accidents were incaution and lack of attention and collision, and trapping, respectively. Limbs were the most affected body parts, and less than 1% of occupational accidents resulted in death. The highest incident was seen in the industrial sector during all years. More severe accident outcomes were seen at older ages and in the male gender, married subjects, winter season, agriculture sector, and outside of work place. Conclusion: These results provide a basis for further investigations regarding data collection and accident causes. Modification of some associated factors and implementation of safety prevention programs would be useful in reducing occupational accidents in Iran.